2008
DOI: 10.1080/09674845.2008.11732800
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between chronic glycaemic control and oxidative stress in type 2 diabetes mellitus

Abstract: This study compares the lipid peroxidation marker urinary thiobarbituric acid reactive substances (TBARS) and antioxidants including plasma alpha-tocopherol (vitamin E), plasma (P-GSH-Px) and erythrocyte glutathione peroxidase (E-GSH-Px) activities, and plasma selenium levels in two groups of type 2 diabetic subjects (both n=20) with a disease duration of < or =2 (GP1) and 4-6 years (GP2), and non-diabetic age and gender-matched control subjects (CG, n=20). The mean (standard deviation [SD]) age of the groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 0 publications
6
47
1
1
Order By: Relevance
“…Our findings are in accordance with previous studies in DM [17][18][19][20][21] and DR patients. 11 However, we could not find reports on both IMA and GSH simultaneously in DM and DR patients.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our findings are in accordance with previous studies in DM [17][18][19][20][21] and DR patients. 11 However, we could not find reports on both IMA and GSH simultaneously in DM and DR patients.…”
Section: Discussionsupporting
confidence: 83%
“…20,21 The mechanisms underlying decreased GSH in diabetes are hyperglycemia-associated metabolic disturbances, abnormal protein balance, and inadequate GSH synthesis leading to OS. 7,20 In line with this, we observed a negative association between FPG and GSH, as hyperglycemia could per se influence oxidant-antioxidant homeostasis. 12 Moreover, GSH may be utilized as an antioxidant to neutralize excess FR generated in diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from earlier epidemiologic investigations showed correlations between abnormal glucose or lipid metabolism and decreased plasma Se concentrations or selenoperoxidase activity in diabetic subjects [41][42][43][44][45][46][47][48]. Likewise, there were also similar correlations or associations in animals.…”
Section: Deficiencies Of Se and Selenoprotein On Diabetessupporting
confidence: 52%
“…239,240 Finally, in some cases the difference in Se status was limited to specific sub-groups such as males 241 or patients with a disease duration r2 years. 234 The latest results from randomized trials confirmed such conflicting data, showing that Se supplementation could either increase the risk of type 2 diabetes or be ineffective. 242,243 As a whole, the association between Se and type 2 diabetes appears to follow a U-shape, so that it may show variable effects depending on the position of the population baseline level of Se intake.…”
Section: Diabetesmentioning
confidence: 99%